8-Isoprostaglandin F2a and ascorbic acid concentration in the aqueous humour of patients with exfoliation syndrome. Issue 3 (1st March 2003) - Koliakos, G G; Konstas, A G P; Schlötzer-Schrehardt, U; Hollo, G; Katsimbris, I E; Georgiadis, N; Ritch, R
Abstract : Background/aim: The authors investigated the concentrations of 8-isoprostaglandin F2a, a marker of oxidative stress in vivo, and ascorbic acid, a protectant against oxidative damage, in the aqueous humour of patients with exfoliation syndrome (XFS) and cataract and compared the results with those in age matched patients with cataract, but without XFS, to determine whether XFS is associated with increased oxidative stress. Methods: Aqueous humour was aspirated at the beginning of phacoemulsification cataract surgery from 27 eyes of 27 cataract patients with XFS and 27 eyes of 27 age matched cataract patients without XFS. 8-Isoprostaglandin F2a concentration in the aqueous was determined with a commercial immunoassay; ascorbic acid concentration was measured with a microplate assay method. Results: . The mean concentration of 8-isoprostaglandin F2a in the aqueous from patients with XFS (2429 (SD 2940) pg/ml; range 400–10500 pg/ml) was significantly higher than that measured in the aqueous of age matched control patients (529.1 (226.8) pg/ml; range 325–1000 pg/ml); (p = 0.0028). Furthermore, mean ascorbic acid concentration in XFS patients (0.75 (0.39) mM; range 0.28–1.70 mM) was significantly lower than that found in control patients (1.19 (0.47) mM; range 0.53–2.4 mM); (p = 0.0005). There was a reverse correlation between 8-isoprostaglandin F2a and ascorbic acid concentration. Conclusion: 8-Isoprostaglandin F2a was significantly increased in the aqueous of patients with XFS, and ascorbic acid was decreased, providing evidence of a role for free radical induced oxidative damage in the pathobiology of XFS.